Sweet Taste Receptor Gene and Caries Trajectory in the Life Course. (April 2023) - Chisini, L.A.; Costa, F.D.S.; Horta, B.L.; Tovo-Rodrigues, L.; Demarco, F.F.; Correa, M.B.
This study aims to investigate whether the trajectory of dental caries in the life course is associated with rs307355 ( TAS1R3 ) and rs35874116 ( TAS1R2 ) and if there is an epistatic association between rs307355 ( TAS1R3 ) and rs35874116 ( TAS1R2 ). A representative sample of all 5, 914 births from the 1982 Pelotas birth cohort was prospectively investigated, and the decayed, missing, and filled teeth (DMF-T) components were assessed at ages 15 ( n = 888), 24 ( n = 720), and 31 ( n = 539) y. Group-based trajectory modeling was used to identify groups with similar trajectories of DMF-T components in the life course. Genetic material was collected, and rs307355 ( TAS1R3 ) and rs35874116 ( TAS1R2 ) were genotyped. Ethnicity was evaluated using ADMIXTURE. Generalized multifactor dimensionality reduction software was used to investigate epistatic interactions. Considering rs307355 ( TAS1R3 ) in the additive effect, the genotype TT was associated with the high decayed trajectory group (odds ratio [OR] = 4.52; 95% confidence interval [CI], 1.15–17.74) and the high missing trajectory group (OR = 3.35; 95% CI, 1.09–10.26). In the dominant effect, the genotype CT/TT was associated with the high decayed trajectory group (OR = 1.64; 95% CI, 1.14–2.35). Allele T was associated with an increased odds of 64% (OR = 1.64; 95% CI, 1.20–2.25) for the decayed component and 41% (OR = 1.41; 95% CI, 1.04–1.92) for the missing component. No associations were observed between rs307355 ( TAS1R3 ) and the filled component. rs35874116 ( TAS1R2 ) was not associated with DMF-T components. Positive epistatic interactions were observed involving rs307355 ( TAS1R3 ) and rs35874116 ( TAS1R2 ) with the decayed component (OR = 1.72; 95% CI, 1.04–2.84). Thus, rs307355 ( TAS1R3 ) genotypes and alleles seem positively associated with the trajectory of decayed and missing components in the life course. Epistatic interaction between rs307355 and rs35874116 may increase the decayed caries trajectory.